2018
DOI: 10.18502/kls.v4i9.3565
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Implementation of Hand Hygiene Practice in Reducing Healthcare-associated Infections: A Systematic Review

Abstract: Healthcare-associated Infections (HAIs) become the priority attentions of health authorities worldwide because it became the most frequent adverse event of infections in the health care system. Hand hygiene is the effective way in preventing HAIs since healthcare personnel's hands frequently serve as vectors in transmission of organism from personnel's hands to patient's, and for that reason, hand hygiene become important to patient safety. Although it is seen as the most important way to reduce HAIs' rate, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…pediatric-friendly reminder posters, pamphlets and increased accessibility of hand sanitizers were proved to improve HCW hand hygiene compliance. 41,46 In our study, capability was not directly linked to hand hygiene behavior but indirectly linked to hand hygiene behavior through motivation, which is an interesting finding. Many studies have revealed that inadequate capability (eg, knowledge and skills) was one of the key reasons for low hand hygiene compliance.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…pediatric-friendly reminder posters, pamphlets and increased accessibility of hand sanitizers were proved to improve HCW hand hygiene compliance. 41,46 In our study, capability was not directly linked to hand hygiene behavior but indirectly linked to hand hygiene behavior through motivation, which is an interesting finding. Many studies have revealed that inadequate capability (eg, knowledge and skills) was one of the key reasons for low hand hygiene compliance.…”
mentioning
confidence: 52%
“…For example, a systematic review indicated that increased accessibility of hand sanitizers and placement of dispensers in more visible places can increase hand hygiene compliance. 41 Moreover, a heavy workload is a barrier to hand hygiene. In some situations, hand hygiene is not being performed because staff are too busy or called away to a more urgent task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations